Synthesis and biological activity of 8-substituted 3-R-xanthines - Aleksandrova, K. V.; Vasylyev, D. A.; Rudko, N. P.; Александрова, Катерина Вячеславівна; Васильєв, Денис Андрійович; Рудько, Наталія Петрівна (Одеса : ГО «Південна фундація медицини», 2020)
Contemporary medicine needs highly effective and low-toxic drugs of diuretic, neurotropic, cardiovascular, and other pharmacological activities. As medications, derivatives of purine and xanthine have found application in practical medicine (purinetol, fludarabine, cladribine, thioguanine, etc.). Consequently, one of the most significant tasks of modern pharmaceutical science is to create novel drugs. In this aspect, special attention should be paid to derivatives of xanthine, which play a vital role in the vigorous processes of plant and animal organisms.